Juvenile delinquency in the USA and Poland based on selected criminal statistics (Archives of Criminology, 2023)
The article discusses the extent and trends of juvenile delinquency in the US and Poland. The text also deals with various types of statistics and databases that we can use when describing the phenomenon of crime. Despite different demographic trends, in both countries we are observing a downward trend in the broadly understood juvenile delinquency, which is considered to be the aggregate of delinquent acts  and status offenses. In the USA, in 1980-2017 the number of arrests decreased by 59.8%, while in Poland the decrease in the number of delinquents - taking into account the period 2000-2018 - amounted to 30%. The most significant impact on the decreasing level of juvenile delinquency in both countries had a decrease in the number of property crimes.